Neutrophils as effector cells in resistance to infection by mycobacterium tuberculosis in HIV-infected individuals - Kroon, Elouise Elizabeth (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.